Polydopamine-coated Au nanorods for targeted fluorescent cell imaging and photothermal therapy - Khlebtsov, Boris Nikolayevich; Burov, Andrey Mikhailovich; Pylaev, Timofey Evgenevich; Khlebtsov, Nikolai G. (Beilstein Journal of Nanotechnology, 2019)
Au nanorods (AuNRs) have attracted a great interest as a platform for constructing various composite core/shell nanoparticles for theranostics applications. However, the development of robust methods for coating AuNRs with a biocompatible shell of high loading capacity and with functional groups still remains challenging. Here, we coated AuNRs with a polydopamine (PDA) shell and functionalized AuNR-PDA particles with folic acid and rhodamine 123 (R123) to fabricate AuNR-PDA-R123-folate nanocomposites. To the best of our knowledge, such AuNR-PDA-based composites combining fluorescent imaging and plasmonic phothothermal abilities have not been reported previously. The multifunctional nanoparticles were stable in cell buffer, nontoxic and suitable for targeted fluorescent imaging and photothermal therapy of cancer cells. We demonstrate the enhanced accumulation of folate-functionalized nanoparticles in folate-positive HeLa cells in contrast to the folate-negative HEK 293 cells using fluorescent microscopy. The replacement of folic acid with polyethylene glycol (PEG) leads to a decrease in nanoparticle uptake by both folate-positive and folate-negative cells. We performed NIR light-mediated targeted phototherapy using AuNR-PDA-R123-folate and obtained a remarkable cancer cell killing efficiency in vitro in comparison with only weak-efficient nontargeted PEGylated nanoparticles. Our work illustrates that AuNR-PDA could be a promising nanoplatform for multifunctional tumor theranostics in the future.
Keywords: Au nanorods; cancer theranostics; fluorescent bioimaging; folate; polydopamine; targeted phototherapy

(untitled) - Dykman, L. A.; Khlebtsov, N. G. (Biomaterials, 2016)

(untitled) - Lammers, T.; Aime, S.; Hennink, W. E.; Storm, G.; Kiessling, F. (Acc. Chem. Res., 2011)

(untitled) - Qin, J.; Peng, Z.; Li, B.; Ye, K.; Zhang, Y.; Yuan, F.; Yang, X.; Huang, L.; Hu, J.; Lu, X. (Nanoscale, 2015)

(untitled) - Zhang, Z.; Wang, J.; Chen, C. (Theranostics, 2013)

(untitled) - Wang, H.; Huff, T. B.; Zweifel, D. A.; He, W.; Low, P. S.; Wei, A.; Cheng, J.-X. (Proc. Natl. Acad. Sci. U. S. A., 2005)

(untitled) - Zhao, T.; Shen, X.; Li, L.; Guan, Z.; Gao, N.; Yuan, P.; Yao, S. Q.; Xu, Q.-H.; Xu, G. Q. (Nanoscale, 2012)

(untitled) - Manohar, S.; Ungureanu, C.; Van Leeuwen, T. G. (Contrast Media Mol. Imaging, 2011)

(untitled) - Jokerst, J. V.; Cole, A. J.; Van de Sompel, D.; Gambhir, S. S. (ACS Nano, 2012)

(untitled) - Kim, K.; Huang, S.-W.; Ashkenazi, S.; O’Donnell, M.; Agarwal, A.; Kotov, N. A.; Denny, M. F.; Kaplan, M. J. (Appl. Phys. Lett., 2007)

(untitled) - von Maltzahn, G.; Centrone, A.; Park, J.-H.; Ramanathan, R.; Sailor, M. J.; Hatton, T. A.; Bhatia, S. N. (Adv. Mater. (Weinheim, Ger.), 2009)

(untitled) - Park, H.; Lee, S.; Chen, L.; Lee, E. K.; Shin, S. Y.; Lee, Y. H.; Son, S. W.; Oh, C. H.; Song, J. M.; Kang, S. H.; Choo, J. (Phys. Chem. Chem. Phys., 2009)

(untitled) - Mackey, M. A.; Ali, M. R. K.; Austin, L. A.; Near, R. D.; El-Sayed, M. A. (J. Phys. Chem. B, 2014)

Cancer Nanotechnology - Huang, H.; El-Sayed, H.; El-Sayed, M. A. (Applications of Gold Nanorods for Cancer Imaging and Photothermal Therapy, 2010)

(untitled) - Alkilany, A. M.; Shatanawi, A.; Kurtz, T.; Caldwell, R. B.; Caldwell, R. W. (Small, 2012)

(untitled) - Ali, M. R. K.; Rahman, M. A.; Wu, Y.; Han, T.; Peng, X.; Mackey, M. A.; Wang, D.; Shin, H. J.; Chen, Z. G.; Xiao, H.; Wu, R.; Tang, Y.; et al. (Proc. Natl. Acad. Sci. U. S. A., 2017)

(untitled) - Smith, D. K.; Korgel, B. A. (Langmuir, 2008)

(untitled) - Zeng, J.-Y.; Zhang, M.-K.; Peng, M.-Y.; Gong, D.; Zhang, X.-Z. (Adv. Funct. Mater., 2018)

(untitled) - Chen, W.-H.; Yang, C.-X.; Qiu, W.-X.; Luo, G.-F.; Jia, H.-Z.; Lei, Q.; Wang, X.-Y.; Liu, G.; Zhuo, R.-X.; Zhang, X.-Z. (Adv. Healthcare Mater., 2015)

(untitled) - Zhang, Z.; Wang, L.; Wang, J.; Jiang, X.; Li, X.; Hu, Z.; Ji, Y.; Wu, X.; Chen, C. (Adv. Mater. (Weinheim, Ger.), 2012)

(untitled) - Fang, S.; Lin, J.; Li, C.; Huang, P.; Hou, W.; Zhang, C.; Liu, J.; Huang, S.; Luo, Y.; Fan, W.; Cui, D.; Xu, Y.; et al. (Small, 2017)

(untitled) - Li, Y.; Wen, T.; Zhao, R.; Liu, X.; Ji, T.; Wang, H.; Shi, X.; Shi, J.; Wei, J.; Zhao, Y.; Wu, X.; Nie, G. (ACS Nano, 2014)

(untitled) - Hu, Y.; Zhou, Y.; Zhao, N.; Liu, F.; Xu, F.-J. (Small, 2016)

(untitled) - Shanmugam, V.; Selvakumar, S.; Yeh, C.-S. (Chem. Soc. Rev., 2014)

(untitled) - Yang, X.; Yang, M.; Pang, B.; Vara, M.; Xia, Y. (Chem. Rev., 2015)

(untitled) - Lee, H.; Dellatore, S. M.; Miller, W. M.; Messersmith, P. B. (Science, 2007)

(untitled) - Zeng, Y.; Liu, W.; Wang, Z.; Singamaneni, S.; Wang, R. (Langmuir, 2018)

(untitled) - Park, J.; Brust, T. F.; Lee, H. J.; Lee, S. C.; Watts, V. J.; Yeo, Y. (ACS Nano, 2014)

(untitled) - Black, K. C.; Yi, J.; Rivera, J. G.; Zelasko-Leon, D. C.; Messersmith, P. B. (Nanomedicine, 2013)

(untitled) - Azab, M. M.; Cherif, R.; Finnie, A. L.; Abou El-Alamin, M. M.; Sultan, M. A.; Wark, A. W. (Analyst, 2018)

(untitled) - Li, N.; Li, T.; Hu, C.; Lei, X.; Zuo, Y.; Han, H. (ACS Appl. Mater. Interfaces, 2016)

(untitled) - Sun, C.; Gao, M.; Zhang, X. (Anal. Bioanal. Chem., 2017)

(untitled) - Wang, S.; Zhao, X.; Wang, S.; Qian, J.; He, S. (ACS Appl. Mater. Interfaces, 2016)

(untitled) - Zhang, L.; Su, H.; Cai, J.; Cheng, D.; Ma, Y.; Zhang, J.; Zhou, C.; Liu, S.; Shi, H.; Zhang, Y.; Zhang, C. (ACS Nano, 2016)

(untitled) - Liu, S.; Wang, L.; Lin, M.; Wang, D.; Song, Z.; Li, S.; Ge, R.; Zhang, X.; Liu, Y.; Li, Z.; Sun, H.; Yang, B.; et al. (ACS Appl. Mater. Interfaces, 2017)

(untitled) - Ge, R.; Li, X.; Lin, M.; Wang, D.; Li, S.; Liu, S.; Tang, Q.; Liu, Y.; Jiang, J.; Liu, L.; Sun, H.; Zhang, H.; et al. (ACS Appl. Mater. Interfaces, 2016)

(untitled) - Luo, J.; Zhang, N.; Liu, R.; Liu, X. (RSC Adv., 2014)

(untitled) - Batul, R.; Tamanna, T.; Khaliq, A.; Yu, A. (Biomater. Sci., 2017)

(untitled) - Ryu, J. H.; Messersmith, P. B.; Lee, H. (ACS Appl. Mater. Interfaces, 2018)

(untitled) - Tao, W.; Zeng, X.; Wu, J.; Zhu, X.; Yu, X.; Zhang, X.; Zhang, J.; Liu, G.; Mei, L. (Theranostics, 2016)

(untitled) - Lynge, M. E.; van der Westen, R.; Postma, A.; Stadler, B. (Nanoscale, 2011)

(untitled) - Nikoobakht, B.; El-Sayed, M. A. (Chem. Mater., 2003)

(untitled) - Khlebtsov, B.; Khanadeev, V.; Khlebtsov, N. (Phys. Chem. Chem. Phys., 2010)

(untitled) - Khlebtsov, B.; Khanadeev, V.; Pylaev, T.; Khlebtsov, N. (J. Phys. Chem. C, 2011)

(untitled) - Hilgenbrink, A. R.; Low, P. S. (J. Pharm. Sci., 2005)

(untitled) - Zhao, T.; Wu, H.; Yao, S. Q.; Xu, Q.-H.; Xu, G. Q. (Langmuir, 2010)

(untitled) - Lakowicz, J. R.; Ray, K.; Chowdhury, M.; Szmacinski, H.; Fu, Y.; Zhang, J.; Nowaczyk, K. (Analyst, 2008)

(untitled) - Fonin, A. V.; Sulatskaya, A. I.; Kuznetsova, I. M.; Turoverov, K. K. (PLoS One, 2014)

(untitled) - Pylaev, T.; Vanzha, E.; Avdeeva, E.; Khlebtsov, B.; Khlebtsov, N. (J. Biophotonics, 2019)

(untitled) - Parakhonskiy, B. V.; Gorin, D. A.; Bäumler, H.; Skirtach, A. G. (J. Therm. Anal. Calorim., 2017)

(untitled) - Xiong, R.; Verstraelen, P.; Demeester, J.; Skirtach, A. G.; Timmermans, J.-P.; De Smedt, S. C.; De Vos, W. H.; Braeckmans, K. (Front. Cell. Neurosci., 2018)

(untitled) - Abadeer, N. S.; Murphy, C. J. (J. Phys. Chem. C, 2016)

(untitled) - Bucharskaya, A.; Maslyakova, G.; Terentyuk, G.; Yakunin, A.; Avetisyan, Y.; Bibikova, O.; Tuchina, E.; Khlebtsov, B.; Khlebtsov, N.; Tuchin, V. (Int. J. Mol. Sci., 2016)

(untitled) - Niidome, T.; Yamagata, M.; Okamoto, Y.; Akiyama, Y.; Takahashi, H.; Kawano, T.; Katayama, Y.; Niidome, Y. (J. Controlled Release, 2006)